Effects of Varying Floorholder Message Content When Using Alternative and Augmentative Communication (AAC) with Voice Output on the Telephone - Kallinen, Megan R. (My University, 2017)
Telephone communication can be difficult for individuals who use augmentative and alternative communication (AAC). This study investigated the effects of various floorholder messages on success of telephone interactions. The researcher called 120 randomly selected businesses in a major midwestern metropolitan area and used AAC with voice output to request business hours. Calls were assigned to one of three floorholder conditions (traditional telephone script, basic floorholder message, or specific instructions) or a no-floorholder condition. Dependent variables included whether the call was successful or unsuccessful (evaluated using a Chi-square analysis), the participant’s reaction to the call, and responses to follow-up interview questions. The researcher analyzed the results of follow-up interview using analysis of variance (ANOVA) and Bonferroni post-hoc testing. Floorholder condition had no effect on the success of the phone calls. Participants in the basic floorholder group reported significantly greater belief that the caller was a real person compared to the control group (no floorholder). No other statistically significant differences were found.